Evaluation of the Implementation of the Family Hope Program (PKH) in the Education Sector in Nagari Guguak Tabek Sarajo, IV Koto District, Agam Regency - Aditiya Fitri; MHD Natsir; Jalius Jalius (Universitas Negeri Padang, 2023)
Lack of collaboration is what inspired this study between groups of recipients of PHK assistance, lack of supervision from government agencies towards the community, lack of realization of layoff funds for educational purposes. So that the general purpose of this study focuses on the implementation of the family of hope program in the field of education in the country of Guguak Tabek Sarojo . the specific objective is to see the evaluation of the family of hope program in the countryof Guguak Tabek Sarojo. This research is a qualitative descriptive type with the research location in Nagari Guguak Tabek Sarajo IV Koto district, Agam Regency. Collection techniques used observation interviews and recording. Analysis techniques used reduction, presentation and inference extraction or confirmation. The findings obtained are that (1) this layoff assistance can increase human resources so as to improve the quality of education for the lower middle class community, (2) program planning in the evaluation of implementation, (3) formative evaluation of program implementation in the education sector has been carried out although there are still few the obstacles experienced (4) the achievement of the summative program in education can be seen from the positive response of the people who receive layoff assistance. It is recommended that the persons in charge work together and coordinate with each other and charge to make a clear structure explaining their respective responsibilities. Keywords: Evaluation, Program, Education, PKH